The use of a user-centric smart mobile application prototype for supporting safety and security in a city: a design science method - Mathijssen, Maxine (Department of Computer Science, 2022)
Cities have always been the drivers of innovation, growth and change. Cities around the world are still rapidly expanding, especially on the African and Asian continents. Cape Town is one of those cities, where urbanisation rates are high, and crime is persisting at alarmingly high levels with crime rates being among the worst in the country and the world. Additionally, the city is home to 7 of 10 worst-performing police services in the country. Combining these factors, there is a need to look at ‘smart' ways of growth which includes facilitating a safe and secure city for citizens. Although Cape Town is pursuing smart initiatives, these have failed to place communities and individuals among the key stakeholders in the smart planning process. This research focuses on further researching smart city initiatives in Cape Town, placing citizens at the centre of the development process. As Cape Town's mobile phone penetration rate is high and access to Internet is rapidly expanding, this research aims to use crowdsourcing techniques for developing a smart mobile application prototype that is focused on enhancing community engagement and facilitating increased perceived feelings of safety and security for citizens. The study uses a Design Science Research method with Cape Town citizens as the main stakeholders, to propose an artifact based on their wishes, needs and current issues faced with regards to safety and security in the city. The proposed artifact focuses on enhancing community engagement, through a chat room and user-logged incident reports, as well as a customised safe route planning functionality where users can send emergency signals to comembers with the use of GPS live location tracking. The research shows participants are willing to adopt the use of the mobile application prototype, given there is substantial community buy-in, and the functionalities in the app are easy to use and quickly accessible. The study further identifies the need for better police follow up and involvement, as the city's police system could benefit from crowd-sourced crime-data in reducing the number of crimes in neighbourhoods to make citizens feel more safe and secure.